2014
DOI: 10.2169/internalmedicine.53.2637
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Complete Response in a Patient with Disseminated Pulmonary Pleomorphic Carcinoma Induced by Cisplatin and Gemcitabine

Abstract: A 47-year-old man was referred to our department due to multiple metastases in the lungs and liver with pleural dissemination six weeks after undergoing curative surgery for lung pleomorphic carcinoma. He received two regimens of chemotherapy, both of which resulted in disease progression. Considering his good general condition, he was treated with cisplatin plus gemcitabine (GP). The metastatic lesions exhibited a complete response after six courses of GP, and the patient has remained free from recurrence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several recent reports have described cases of PPC that responded to cytotoxic chemotherapy containing platinum and gemcitabine [ 8 12 , 23 ]. Tamiya et al mentioned that high expression of human equilibrative nucleoside transporter 1 (hENT1), the major transporter of gemcitabine, might be associated with high sensitivity to gemcitabine in PPC [ 12 ]. We also experienced one patient who achieved long-term stable disease without progression after receiving cisplatin and gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports have described cases of PPC that responded to cytotoxic chemotherapy containing platinum and gemcitabine [ 8 12 , 23 ]. Tamiya et al mentioned that high expression of human equilibrative nucleoside transporter 1 (hENT1), the major transporter of gemcitabine, might be associated with high sensitivity to gemcitabine in PPC [ 12 ]. We also experienced one patient who achieved long-term stable disease without progression after receiving cisplatin and gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical outcome is stage-dependent, it follows a more aggressive clinical course and has a worse prognosis than other histological types of NSCLC [ 6 10 ]. Furthermore, some recent reports have noted that PPC is often refractory to chemotherapy regimens which provide active treatment for NSCLC [ 8 12 ]. Due to its rarity, no optimal treatment for PPC has yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al resported cisplatin and vinorelbine were effective as a neo-adjuvant therapy for PPC patients [ 29 ]. Some reports have mentioned that a regimen involving gemcitabine or taxanes is effective [ 12 , 30 , 31 ]. In our study, we found that patients who received chemotherapy had better OS than patients without chemotherapy and chemotherapy were found to be independently associated with the survival, especially in the distant stage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some PPC cases treated with cytotoxic chemotherapy have been reported, but the median OS was only 7–8 months. Some reports have mentioned that a regimen involving gemcitabine or taxanes is effective. Tamura et al .…”
Section: Discussionmentioning
confidence: 99%